Clinical field site evaluation of the FACSCount for absolute CD3+, CD3+ CD4+, and CD3+ CD8+ cell count determinations in Thailand. - Young, N L (1997)
The FACSCount flow cytometer absolute CD3+, CD3+ CD4+, and CD3+ CD8+ cell counts measured at a field site hospital laboratory in Thailand were compared to FACScan absolute counts obtained at a nearby research laboratory. Correlation coefficients for 208 samples were > or = 0.95. The FACSCount was accurate, and it was easier and less expensive to operate than the FACScan. Additionally, the FACScan-generated lymphocyte percentage value was accurate for use with the FACScan SimulSET software.